2013
DOI: 10.3758/s13423-013-0439-7
|View full text |Cite
|
Sign up to set email alerts
|

“Moving to the beat” improves timing perception

Abstract: Here, we demonstrate that "moving to the beat" can improve the perception of timing, providing an intriguing explanation as to why we often move when listening to music. In the first experiment, participants heard a series of isochronous beats and identified whether the timing of a final tone after a short silence was consistent with the timing of the preceding sequence. On half of the trials, participants tapped along with the beat, and on half of the trials, they listened without moving. When the final tone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
104
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(123 citation statements)
references
References 39 publications
11
104
1
2
Order By: Relevance
“…First, complementing Ohriner's point regarding the distinction between late and early taps, listeners have been shown to be more accurate in detecting late versus early events (Large & Jones, 1999;Manning & Schultz, 2013), while musicians were found to be better at coordinating with decreasing rather than increasing tempi (Loehr, Large, & Palmer, 2011). Second, the author rightly points out that agreement between performer and listener on the direction of tempo change (acceleration or deceleration), even in cases where the listener underestimates a deceleration, is quite different from an inaccurate tap in the opposite direction of the actual tempo change.…”
Section: Synchronicity Musical Tension and Familiaritymentioning
confidence: 99%
See 1 more Smart Citation
“…First, complementing Ohriner's point regarding the distinction between late and early taps, listeners have been shown to be more accurate in detecting late versus early events (Large & Jones, 1999;Manning & Schultz, 2013), while musicians were found to be better at coordinating with decreasing rather than increasing tempi (Loehr, Large, & Palmer, 2011). Second, the author rightly points out that agreement between performer and listener on the direction of tempo change (acceleration or deceleration), even in cases where the listener underestimates a deceleration, is quite different from an inaccurate tap in the opposite direction of the actual tempo change.…”
Section: Synchronicity Musical Tension and Familiaritymentioning
confidence: 99%
“…Moreover, Ohriner's experiment incorporates several elements that have been at the forefront of recent research on rhythm perception. Notably, it has been shown that participants tapping along with the beat were more accurate in predicting the timing of a final tone than participants listening without moving (Manning & Schultz, 2013) and, more generally, that body movement enhances auditory temporal sensitivity (Su & Pöppel, 2011).…”
mentioning
confidence: 99%
“…The notion that perception is active is an old one, from at least the time of Helmholtz, but one that is currently attracting a large amount of attention in neuroscience in general [44] and more specifically in the area of rhythm perception [31,32,[45][46][47]. These accounts build either on the dynamic attending theory of Jones (e.g.…”
Section: Motor Influences On Perceptionmentioning
confidence: 99%
“…London (2011) also found that the attentional focus of the listener affected tempo judgments. Moving along with the music also affects our perception of it: Manning and Schutz (2013) found that tapping along enhanced the detection of perturbed tones, and London and Cogsdill (2011) found that self-motion influenced perceived tempo for some listeners.…”
Section: Introductionmentioning
confidence: 99%